The Deformation Responses As The Resulted Of The Tectonics In Apaumagida (Apowo), Enarotali And Legare Mountain Area of Papua Province - Gultom, Maran; Dandy Waromi, Doodle; Abdurrachman, Mirzam; Yaner Ayomi , Iwan; Steven Wetipo, Yafet; Disti Mambrasar , Ela (International Journal of Science, Technology & Management, 2024)
The deformation phenomenon in Central Mountain of Papua Province is very complex, isn’t there the uniformity of geology structure pattern (folds, joints, faults) as resulted of tectonics or reactivations of the geology structure of the lately rock to the upper early rock?. Therefore, measuring the geology structure had to be done with the surface geological mapping and the measured section traverse in the field. The research area distributed in three boundaries of tectonics in coordinate 135° 00’ 00” East - 136° 30’ 00” East and 3° 00’ 00” South - 4° 40’ 00” South. There are three research areas namely the Apaumagida area represent the Permian – Triassic Periods in coordinate 135°18’11,88” East - 135°43’20,14” East and 3°56’17,59” South - 4°8’28,44” South, the Enarotali area represent the Cretaceous – Paleocene Periods in coordinate 136°18’45,08” East - 136°29’42,00” East and 3°53’34,75” South - 4°5’16,03” South, and the Legare Mountain area represent the Tertiary – Quaternary Periods in coordinate 135° 28’ 54,87” East - 135° 47’ 16,80” East and 3° 25’ 31,17” South - 3° 6’ 6,25” South. According to the result and discussion, conclusioned that the direction of folds, jonts, faults were different between the oldest periods to the youngest periods, indicated by the direction diffrent of principal stress on N 5° – 27°E in Permian Period, N 349° - 358°E in Triassic Period, N 15° – 32°E in Cretaceous period, N 45° 54° E in Paleocene Period, N52° – 74°E in Tertiary Period N74°-78° E in Quarternary. Therefore, there were general pattern in the diffrent of folds, joints and faults from Permian – Triassic and Cretaceous – Paleocene but there’s conformity from the Tertiary – Quarternary. The general conclusion that the tectonic is actively roled for the geology structure developing in Central M.ountain area since Paleozoic to Quaternary.